Erratum on the article ‘Non-linear dynamic analysis of coupled spar platform’ (DOI:10.3846/13923730.2013.768546) - Jameel, Mohammed; Ahmad, Suhail; Islam, A. B. M. Saiful; Jumaat, Mohd Zamin (Journal of Civil Engineering and Management, 2013)
Erratum on the article ‘Non-linear Dynamic Analysis of Coupled Spar Platform’ (doi: 10.3846/13923730.2013.768546). Journal of Civil Engineering and Management, 19(5), p. 772.